2009
DOI: 10.1063/1.3151690
|View full text |Cite
|
Sign up to set email alerts
|

Co layer fragmentation effect on magnetoresistive and structural properties of nanogranular Co/Cu multilayers

Abstract: We deposited nanogranular Co/Cu multilayers made of thin fragmented Co layers separated by thicker Cu layers to study how the structure and the microstructure of magnetic nanogranular samples change as the average particle size is reduced, and how these changes affect the giant magnetoresistive response of the samples. Indeed, thanks to the vertical periodicity of the structure, namely to the fact that Co/Cu interfaces display an ordered stacking and are not randomly distributed within the samples as in conven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2013
2013

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 56 publications
0
1
0
Order By: Relevance
“…The integration method was introduced without proof or derivation by Salditt and followed by several other studies (Spizzo et al, 2009;Siffalovic et al, 2010a,b). In this work we reviewed the integration method and surprisingly found that it is not generally correct though its basic idea is inspiring.…”
Section: Introductionmentioning
confidence: 99%
“…The integration method was introduced without proof or derivation by Salditt and followed by several other studies (Spizzo et al, 2009;Siffalovic et al, 2010a,b). In this work we reviewed the integration method and surprisingly found that it is not generally correct though its basic idea is inspiring.…”
Section: Introductionmentioning
confidence: 99%